Violencia intrafamiliar como factor de riesgo para la gestante y su hijo/hija - Tenezaca Medina, Andrea Yadira (2014)
Violence against pregnant institutes a major issue, in which the abuse of such women and children is linked in multiple ways. The objective of this research work is to associate exposure Domestic violence during pregnancy with obstetric and perinatal complications. A study of cases and controls in the HIAL, in a sample of 116 postpartum women and their newborns, we determined the group of cases as those who had more than 2 obstetric complications was performed, exposure was based on a questionnaire, consisting of five questions, which investigate the experience of psychological, physical and sexual violence were answered with "yes" or "no." Results: The prevalence of exposure to the VI was 19.86%. The psychological type with 52% was the most frequent. Abused women were 2.77 times more risk of obstetric complications, perinatal death and violence associated statistically mother. Keywords: violence, abuse, pregnant, son, daughter, risk factor.